Wasp venom peptide as a new antichagasic agent. (15th July 2020) - Freire, Katielle Albuquerque; Torres, Marcelo Der Torossian; Lima, Dânya Bandeira; Monteiro, Marilia Lopes; Bezerra de Menezes, Ramon Róseo Paula Pessoa; Martins, Alice Maria Costa; Oliveira Jr, Vani Xavier
Abstract: Chagas disease is caused by Trypanosoma cruzi and affects approximately 10 million people a year worldwide. The only two treatment options, benznidazole and nifurtimox, have low efficacy and high toxicity towards human cells. Mastoporan peptide (MP) a small cationic AMP from the venom of the wasp Polybia paulista has been reported as a potent trypanocidal agent. Thus, we evaluated the antichagasic effect of another AMP from the venom of the same wasp Polybia paulista, polybia-CP (ILGTILGLLSKL-NH2 ), and investigated its mechanism of action against different stages of the trypanosomal cells life cycle. Polybia-CP was tested against the epimastigote, trypomastigote and amastigote forms of the T. cruzi Y strain (benznidazole-resistant strain) and inhibited the development of these forms. We also assessed the selectivity of the AMP against mammalian cells by exposing LLC-MK2 cells to polybia-CP, the peptide presented a high selectivity index (>106). The mechanism of action of polybia-CP on trypanosomal cells was investigated by flow cytometry, scanning electron microscopy (SEM) and enzymatic assays with T. cruzi GAPDH (tcGAPDH), enzyme that catalyzes the sixth step of glycolysis. Polybia-CP induced phosphatidylserine exposure, it also increased the formation of reactive species of oxigen (ROS) and reduced the transmembrane mitochondrial potential. Polybia-CP also led to cell shrinkage, evidencing apoptotic cell death. We did not observe the inhibition of tcGAPDH or autophagy induction. Altogether, polybia-CP has shown the features of a promising template for the development of new antichagasic agents. Graphical abstract: Image 1 Highlights: Polybia-CP was able to inhibit all main forms of Trypansoma cruzi. Polybia-CP showed high selectivity index (>106). Polybia-CP mechanism of action showed apoptotic involviment. Action mechanism showed no evidences of tcGAPDH inhibition or autophagy.